2010
DOI: 10.1371/journal.pone.0011405
|View full text |Cite
|
Sign up to set email alerts
|

Transgene × Environment Interactions in Genetically Modified Wheat

Abstract: BackgroundThe introduction of transgenes into plants may cause unintended phenotypic effects which could have an impact on the plant itself and the environment. Little is published in the scientific literature about the interrelation of environmental factors and possible unintended effects in genetically modified (GM) plants.Methods and FindingsWe studied transgenic bread wheat Triticum aestivum lines expressing the wheat Pm3b gene against the fungus powdery mildew Blumeria graminis f.sp. tritici. Four indepen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

9
75
2
1

Year Published

2011
2011
2021
2021

Publication Types

Select...
6
3
1

Relationship

1
9

Authors

Journals

citations
Cited by 82 publications
(87 citation statements)
references
References 50 publications
9
75
2
1
Order By: Relevance
“…different gene expression levels as a consequence of different location of the 350 insertion site (Cubas et al 1999, Filipecki andMalepszy 2006). Such expression differences were 351 for example observed in a previous study using multiple transformation events with a single Pm3 352 allele (Zeller et al 2010). …”
Section: Differences Among Gm Lines 337mentioning
confidence: 87%
“…different gene expression levels as a consequence of different location of the 350 insertion site (Cubas et al 1999, Filipecki andMalepszy 2006). Such expression differences were 351 for example observed in a previous study using multiple transformation events with a single Pm3 352 allele (Zeller et al 2010). …”
Section: Differences Among Gm Lines 337mentioning
confidence: 87%
“…For GM traits, as for any novel gene variation investigation, it has been demonstrated that the effect obtained in a highly controlled environment could differ drastically in more variable growing conditions [19]. We have shown this to be the case for GWD RNAi for overall yield, where the Despite the use of an endosperm-specific promoter, increases in biomass were found for GWD RNAi lines during development in the glasshouse.…”
Section: Resultsmentioning
confidence: 71%
“…For Bobwhite and Frisal, each had a transgenic line and its corresponding control line. The transgenic line of Bobwhite (Pm3b#1) carries the transgene Pm3b of hexaploid wheat, which confers race-specific resistance to wheat powdery mildew [6]. The null-segregant line Sb#1 was used as the corresponding control line.…”
Section: Methodsmentioning
confidence: 99%